Juridical Analysis of Constitutional Court Decision No. 85/PUU-XIV/2016: Examining the Legal Implications of the Law on Regional Head Elections (Law No. 10/2016) - Irman Putra; Arief Fahmi Lubis (Westscience Press, 2023)
This paper provides a juridical analysis of the Constitutional Court Decision No. 85/PUU-XIV/2016, which examines the legal implications of the Regional Head Election Law (Law No. 10/2016). It explores the constitutional context and rationale behind the decision, emphasising its impact on the legal framework governing regional head elections in Indonesia. By dissecting the Constitutional Court's reasoning and the legal principles applied, the analysis aims to explain the impact of the ruling on the democratic process, electoral integrity, and governance at the local level. The findings highlight a significant legal precedent and underline the role of the ruling in shaping future electoral regulations and practices in Indonesia.